Addressing the choices of contemporaries in the stock market - Khaled Ibrahim, Ibrahim (Opción, 2019)
Aim: To address the available sales options of contemporary jurists in the stock market and Shari’a. Subject and Methods: To restudy the opinions of previous jurists of the past Islamic era about this issue and to evaluate the sharia's law agrees with this issue. Results: contracts are an investment tool developed in the financial markets that investors use as a precaution against the risks of changing stock prices and foreign exchange rates, and a way to maximize their profits in the shor- test and fastest way by speculating on price differentials. Conclusion: Contracts, as they are now practiced in the financial markets in their current form, do not fall under any of the names of the named contracts, but in violation of the so-called contracts in all Islamic jurisprudence. There is no connection between them and the choices in Islamic jurisprudence